2022
DOI: 10.1111/ddg.14882
|View full text |Cite
|
Sign up to set email alerts
|

Dermatofibrosarcoma protuberans of the face: A clinicopathologic and molecular study of 34 cases

Abstract: Summary Background Dermatofibrosarcoma protuberans (DFSP) is one of the most common dermal sarcomas, but facial DFSP is rare. Patients and Methods The clinicopathological characteristics of 34 facial DFSPs were reviewed. Additional immunostaining (CD34) and PDGFB/COL1A1‐PDGFB fluorescence in situ hybridization (FISH) detection were performed. Results Patients were aged from 24 to 64 years (mean 42.9 years), with a male‐to‐female ratio of 4.7 : 1. Morphologically, classic DFSP (25/34, 73.5 %), pigmented DFSP (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…4 A recent clinicopathologic study of 34 patients with DFSPs revealed a greater incidence of myxoid degeneration in patients with FS-DFSPs, as well as a worse prognosis, which warrants more concern in treatment and follow-up. 7 Dermatofibrosarcoma protuberans infiltrates in a peculiar tentacle-like pattern, which makes complete excision with negative margins crucial to reduce recurrence. Wide local excision with a margin of 2-5 cm or MMS remains the mainstay treatment.…”
mentioning
confidence: 99%
“…4 A recent clinicopathologic study of 34 patients with DFSPs revealed a greater incidence of myxoid degeneration in patients with FS-DFSPs, as well as a worse prognosis, which warrants more concern in treatment and follow-up. 7 Dermatofibrosarcoma protuberans infiltrates in a peculiar tentacle-like pattern, which makes complete excision with negative margins crucial to reduce recurrence. Wide local excision with a margin of 2-5 cm or MMS remains the mainstay treatment.…”
mentioning
confidence: 99%